Mechanics of Composite, Hybrid and Multifunctional Materials, Volume 5 Proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics - Thakre, Piyush R.; Singh, Raman P.; Slipher, Geoffrey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Mechanics of Composite, Hybrid, and Multifunctional Materials, Volume 5 of the Proceedings of the 2018 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the fifth volume of eight from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of areas, including: Recycled Constituent Composites Nanocomposites Mechanics of Composites Fracture & Fatigue of Composites Multifunctional Materials Damage Detection & Non-destructive Evaluation Composites for Wind Energy & Aerospace Applications Computed Tomography of Composites Manufacturing & Joining of Composites Novel Developments in Composites.
Keywords: Mechanics, Applied; Solids; Ceramic materials; Materials -- Analysis; Solid Mechanics; Ceramics; Characterization and Analytical Technique